Sistematización de un proceso de intervención con cinco familias con un miembro que presente síntomas de drogodependencia en una instancia de salud pública en el norte de Quito, desde la exploración de experiencias vinculadas a la deprivación afectiva en el período marzo-julio del 2021, desde un enfoque sistémico, articulado al psicoanálisis de Winnicott - Moncayo Galárraga, Karla Stefanía (2022)
This document collects the learning achieved in the process of accompanying five families with a member who presents symptoms of drug dependence in a public health instance north of Quito in the year 2021. Drug use constitutes a public health problem due to the high rate of consumers in Ecuador and the serious physical, psychological and socio-family consequences that it produces. Drug addiction is a phenomenon that needs to be explored from a comprehensive approach, therefore, the need arises to provide psychological support to families suffering from this symptomatology. And thus, be able to understand the personal, family and social risk factors linked to this problem. For the present study, Murray Bowen's systemic theory was borrowed, taking into consideration the level of family differentiation, the projection process that is transmitted from the original system to the current one, and the emotional cut, under the analysis of the psychosocial category of the deprivation proposed by the psychoanalyst Donald Winnicott. This intervention was based on a participant observation methodology with the five families, which allowed exploring the internal dynamics of the family. To carry out the analysis of the indicated experience, a qualitative, descriptive approach and documentary review were used to explore the behavior of the human being in his family system from affective deprivation and its incidence in the consumption of substances from the aforementioned phenomena.